Nepita Conferta A House Moth Caterpillar Causing Contact And Air Borne Lepidopterism In India And Its Manahgement - Dr.DK GAUTAM; BABITA CHOUDHARY; PARUL BHOURGADE; MK GAUTAM (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2025)
Caterpillars are immature stages of moths and butterflies. A new species of a house hold caterpillar mostly found under the clay roof tiles of wooden house and buildings in India. This species is reported in village Tighara and surrounding villages in District Seoni and District Balaghat of state Madhay Pradesh in central India (DMS 22° 5′ 24″ N, 79° 33′ 0″ E). This Caterpillar is more harmful for humans which are living with them in the same places and they remains for long times of years even in their dead conditions. These caterpillars completes their life cycle in non-living things like wooden materials, houses and everywhere where sweeping is not possible. When the urticating hairs comes in contact via air or direct touch with human skin by any means the urticating hairs that releases Thaumetopoein causes itching ,irritation and contact dermatitis (COD) for a week. We intendant to this research because this caterpillar species is new for scientists and unreported yet in scientific Journals. It appears in a large numbers in August and September month. So many villagers affected by Contact Dermatitis (COD) disease for several years because the dry caterpillar’s hairs also cause contact and air born dermatitis.